Lung Volume Reduction in Chronic Obstructive Pulmonary Disease (COPD) AND#8211; An Updated Review of Surgical and Endoscopic Procedures - Ramakant Dixit (Archives of Clinical and Experimental Surgery, 2012)
The conventional medical management of emphysema using bronchodilators and anti-inflammatory agents has a limited benefit in patients having advanced hyperinflation of lungs due to destruction of elastic tissue. The natural course of Chronic Obstructive Pulmonary Disease (COPD) has been shown to be altered by only smoking cessation and oxygen therapy so far. The lung volume reduction surgery is viewed as another modality to change the natural history of emphysema in recent years. For patients with more generalized emphysema, resection of lung parenchyma improves elastic recoil and chest wall mechanics. An extensive literature search has demonstrated that carefully selected patients of emphysema (i.e. upper lobe predominant disease, low exercise capacity and Forced Expiratory Volume in First Second (FEV1) and DLco and #8804; 20% of predicted) receive benefits in terms of symptomatic improvement and physiologic response following Lung Volume Reduction Surgery (LVRS). The resurgent interest in LVRS and National Emphysema Treatment Trial findings for emphysema have stimulated a range of innovative methods, to improve the outcome and reduce complications associated with current LVRS techniques. These novel approaches include surgical resection with compression/banding devices, endobronchial blockers, sealants, obstructing devices and valves and endobronchial bronchial bypass approaches. Experimental data and preliminary results are becoming available for some of these approaches. Most of the published studies so far have been uncontrolled and unblinded. Overall, extensive research in the near future will help to determine the potential clinical applicability of these new approaches to the treatment of emphysema symptoms. [Arch Clin Exp Surg 2012; 1(4.000): 249-257]